Implementation of the Generation Gender (GEN-G) Rutgers Internasional Program in Gender Based Violence (GBV) Cases in Indonesia in 2023-2024 - Putri Nabila; Agung Prija Utama; Sintia Catur Sutantri; Risalatu Mirajiah (Al-Makki Publisher, 2025)
Gender-Based Violence (GBV) remains a pervasive human rights violation globally and a critical barrier to achieving Sustainable Development Goal 5 on gender equality. In Indonesia, the high number of reported GBV cases underscores the urgent need for effective intervention strategies. This research examines the implementation of the Generation Gender (Gen-G) program initiated by Rutgers International in addressing Gender-Based Violence (GBV) in Indonesia during the 2023–2024 period. As a transnational advocacy initiative, the program seeks to promote gender justice through youth empowerment and the institutional strengthening of civil society organizations in Jakarta, Bandung, and Palu. Employing a qualitative descriptive method and grounded in Keck and Sikkink’s Transnational Advocacy Networks (TANs) theory, the research analyzes Rutgers’ strategic use of four key tactics: information politics, symbolic politics, leverage politics, and accountability politics. The findings reveal that Rutgers International has successfully established strategic advocacy networks with local actors such as Yayasan Gemilang Sehat Indonesia, Koalisi Perempuan Indonesia, and LBH APIK, enabling a context-specific and inclusive response to GBV. Despite these advances, structural barriers, deeply rooted patriarchal norms, and limited policy support remain significant challenges to full program effectiveness. This study underscores the critical role of transnational networks and multi-sectoral collaboration in advancing gender-sensitive policy reform and social transformation. Furthermore, it contributes to the broader discourse in international relations by highlighting the strategic influence of non-state actors in the diffusion of global gender norms at the local level.